Drought response of biotic-stress tolerant accessions of black pepper (Piper nigrum L.) - KM, Prakash; Joseph, Jiji; AV, Santhoshkumar; KV, Saji; Puthiamadom, Neeraja; Ramachandran, Arjun (Journal of Tropical Agriculture, 2024)
Abstract Tandem selected 20 superior accessions of black pepper having better yield and biotic stress tolerance were evaluated for drought response along with drought tolerant black pepper variety, Panniyur-5 under controlled condition. Physiological responses of accessions were evaluated under 5 and 10 days of drought induction. Accessions did not differ for physiological parameters under field capacity without stress. All the physiological parameters except leaf temperature got reduced continuously at fifth and tenth days of drought induction. More than 50 per cent reduction was observed for mean value for photosynthesis, stomatal conductance, chlorophyll content and chlorophyll stability index after 10 days of drought induction. The accessions IC 598869 and IC 598890 ranked better than the drought tolerant variety P5, can be tested further for yield and other attributes to release as a variety.